1974
DOI: 10.1007/bf02371511
|View full text |Cite
|
Sign up to set email alerts
|

Influence of parasitoid-host density and host availability on the laboratory propagation ofMicroctonus aethiops [Hym.: Braconidae] parasitoid ofHypera postica [Coleop.: Curculionidae]

Abstract: Laboratory studies of the arrhenotokous braconid wasp, Microctonus aethiops /NEEs) were conducted relative to maximizing parasitoid production without adversely affecting sex ratios of the progeny.The influence of host Hypera postica (GYLLE.~rlaL} and parasitoid densities on parasitoid productivity was evaluated. Maximum production or a mean 25.8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 3 publications
2
7
0
Order By: Relevance
“…Moreover, the pattern whereby most oviposition occurred early in the M. hyperodae life-span is similar to that observed in M. aethiopoides (Loan & Holdaway, 1961). Fusco and Hower (1974) found that at 23 ~ this species laid 41.7 % of its eggs in the first two days after mating. This is not necessarily typical of Microctonus spp.…”
Section: The Longevity and Fecundity Of M Hyperodae Longevitysupporting
confidence: 68%
See 1 more Smart Citation
“…Moreover, the pattern whereby most oviposition occurred early in the M. hyperodae life-span is similar to that observed in M. aethiopoides (Loan & Holdaway, 1961). Fusco and Hower (1974) found that at 23 ~ this species laid 41.7 % of its eggs in the first two days after mating. This is not necessarily typical of Microctonus spp.…”
Section: The Longevity and Fecundity Of M Hyperodae Longevitysupporting
confidence: 68%
“…The realised fecundity of M. hyperodae appeared to be greater than that of M. aethiopoides attacking adult H. postica (Fusco & Hower, 1974), similar to that of M. colesi (Drea et al, 1972) but relatively modest compared to other Microctonus spp. (table 3).…”
Section: The Longevity and Fecundity Of M Hyperodae Longevitymentioning
confidence: 89%
“…The sex ratio of Microctonus sp. under natural conditions was from 0.57 ± 0.11 to 0.69 ± 0.10, which is close to 1 male : 2 female, very close to 0.60-0.65 found in the nature in M. aethiops (Nees) (= aethiopoides Loan) by Fusco & Hower (1974). In the laboratory, the sex ratio ranged from 0.16 ± 0.13 to 0.37 ± 0.13 (Table 1), with a predominance of male parasitoids.…”
Section: Resultssupporting
confidence: 77%
“…In the New Zealand, the mean parasitism rate of L. bonariensis by Microctonus hyperodae was 58.7% (Goldson et al, 1993), with a ratio of 40 beetles : 1 female parasitoid. Fusco & Hower (1974) found a maximum parasitism of 51.6% when Hypera postica was parasitized by M. aethiops with 50:1 ratio, with a low percentage of premature mortality.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation